ANALISIS PAJAK PENGHASILAN PASAL 23 ATAS JASA LAIN LAIN PADA PT. SIBA PRIMA UTAMA FEED MILL TAHUN 2016 - Abdullah, Adida Setyawan; Samrotun, Yuli Chomsatu; ., Suhendro (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
The research aims to analyze the application of PPh Pasal 23 the basic income tax imposition, calculation, remittance, and reporting. This research is descriptive research. In this study is from the PPh Pasal 23 of others. The population of this research is the lease transaction to the service during the year 2016. This research does not use the samples in the researching object of lease transactions but will check all transactions related to PPh Pasal 23 PT Prima Utama Siba Feed Mill. The results of this research are the basis for the imposition of a transaction over article 23 other services against an individual are not appropriate, because the object of PPh Pasal 23 is a business entity remains.